Digital Conversion of Analogue Cadastral Maps of Kathmandu Metropolitan City - Acharya, Babu Ram; Baral, Toya Nath; Subedi, Nab Raj (Journal on Geoinformatics, Nepal, 2004)
Land is the olny immovable property that can be used as a means for agricultural production as well as a means for mortgage for financing industrial or commercial enterprises. Spatial technologies play a key role in managing our land, water and natural resources. Cadastral data is a major component for the development of Land Infromation system. Therefore, systematic land registration system based on accurate and scientific cadastral map are found inevitable for poverty alleviation, good governance and women empowerment through security of their rights on property as well as the planning and development of a sustainable environmental protection within Metropolitan city. Digital cadastral parcel is the fundamental spatial unit on which database is designed, created, maintained and operated. Availability of accurate and updated cadastral maps is a primary requisite for successful planning, policy formulating and maintenance of city utility services, which meed cadastral and utility information together. Flawed cadastral maps can put land, revenue and taxation system at stake. Kathmandu, the capital city of Nepal still is lacking utility maps combining cadastral information with the utility. There is an urgent need to have an effective, accurate and easy to access land revenue and utility services system within the urban areas which could be achieved after the production of reliable base maps and land registration system to guarantee land allocation and property rights which can well be achieved by digitla conversion and correction of base cadastral maps. This paper highlights the drawbacks of the conventional cadastral maps and the possible advantages of digital cadastral maps over these. Also the problems, issues and implications during digital conversion and creating database of the same will be discussed.